Isolation of Highly Pathogenic H5N1 Influenza Viruses in 2009–2013 in Vietnam - Zhong, Gongxun; Fan, Shufang; Lopes, Tiago J. S.; Le, Mai Quynh; van Bakel, Harm; Dutta, Jayeeta; Smith, Gavin J. D.; Jayakumar, Jayanthi; Nguyen, Hang Le Khanh; Hoang, Phuong Vu Mai; Halfmann, Peter; Hatta, Masato; et al. (Frontiers in Microbiology, 2019)
Routine surveillance and surveillance in response to influenza virus outbreaks in avian species in Vietnam in 2009–2013 resulted in the isolation of numerous H5N1 influenza viruses of clades 1.1.2, 2.3.2.1a, 2.3.2.1b, 2.3.2.1c, and 2.3.4.1. Consistent with other studies, we found that viruses of clade 2.3.2.1c were dominant in Vietnam in 2013 and circulated in the northern, central, and southern parts of the country. Phylogenetic analysis revealed reassortment among viruses of clades 2.3.2.1a, 2.3.2.1b, and 2.3.2.1c; in contrast, no reassortment was detected between clade 2.3.2.1 viruses and viruses of clades 1.1.2 or 2.3.4.1, respectively. Deep-sequencing of 42 of the 53 isolated H5N1 viruses revealed viral subpopulations encoding variants that may affect virulence, host range, or sensitivity to antiviral compounds; viruses isolates containing these subpopulations may have a higher potential to transmit and adapt to mammals. Among the viruses sequenced, relatively high numbers of non-synonymous nucleotide polymorphisms were detected in three viruses isolated from barn swallows, possibly suggesting influenza virus adaption to this host.